Correction to: The surgical outcomes of fixing ipsilateral femoral neck and shaft fractures: single versus double implants fixation - Yahya Alborno (14158818) (2022)
Correction: The surgical outcomes of fixing ipsilateral femoral neck and shaft fractures: single versus double implants fixation: http://dx.doi.org/10.1007/s00590-022-03312-0, published online: 04 July 2022. The original version of this article unfortunately contained a mistake. The author name Abdullah M. Abunimer was incorrectly written as Abdullah Abunimer. Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00590-022-03411-y